Pengukuran Mean Length of Utterance dalam Menilai Perkembangan Pemerolehan Bahasa Anak Usia Dini : Kajian Psikolinguistik - Rahma Andien Arezsya; Fransiska Homer (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to analyze the language development of early childhood through measuring Mean Length of Utterance (MLU) and identifying word classes, word types, and sentence patterns produced by children. The background of this research focuses on the importance of language as a communication tool and foundation in children's cognitive and social development. The method used was descriptive qualitative involving two subjects, Cheira Arumi Nasution and Abram Berger, aged 3 years and 2 months and 2 years and 7 months respectively. Data were collected through indirect observation techniques by recording children's speech and analyzing 100 utterances from each subject. The findings show that Cheira Arumi has an MLU of 3.48, which places her at stage IV, while Abram Berger has an MLU of 1.76, which indicates that he is at stage II. Both subjects showed that their word length was still not in line with their age standard according to MLU. This study emphasizes the importance of parents' role in providing more intensive language stimulation and reducing the use of gadgets to support children's language development.